Alat Siram Bawang Merah Otomatis Terintegrasi Battery Charging Station Berbasis Panel Surya - Dimas Anton Asfani; I Made Yulistya Negara; I Gusti Ngurah Satriyadi Hernanda; Daniar Fahmi; Titiek Suryani; Devy Kuswidiastuti; Puji Handayani (Sewagati, 2026)
The village of Sumberbulu, Tegalsiwalan District, Probolinggo Regency is an area where the majority of the population earns a living as shallot farmers. As a result, Probolinggo Regency has become the largest supplier of shallots in East Java. However, this has not been matched by the application of technology in shallot cultivation. Farmers still use manual methods and rely solely on their own labor. To address this issue, Alfin, a red onion farmer's son, proposed the use of environmentally friendly electric pumps integrated with solar cells. The use of renewable energy is particularly suitable for Sumberbulu Village, as it has high solar irradiance. This innovative project is supported by the High Voltage Laboratory of the ITS Department of Electrical Engineering as a form of community service, with the hope of increasing the productivity of shallot farmers, supporting economic growth, and achieving the goal of sustainable technology development. The implementation of this community service is expected to produce the following outputs: the creation of a red onion watering tool and the installation of a solar cell-integrated charging station, socialization to the community, progress reports and final reports, national journals, book chapters, popular media news, and activity videos. Keywords: Onion Irrigation Tool, Sumberbulu Village, Red Onion Farmer Productivity, Solar Cell, Battery Charging Station